Robust Adaptive Modified Newton Algorithm for Generalized Eigendecomposition and Its Application. (8th August 2007) - Yang Yang, Jian Jian; Yang Yang, Feng Feng; Xi Xi, Hong-Sheng Hong-Sheng; Guo Guo, Wei Wei; Sheng Sheng, Yanmin Yanmin
Abstract : We propose a robust adaptive algorithm for generalized eigendecomposition problems that arise in modern signal processing applications. To that extent, the generalized eigendecomposition problem is reinterpreted as an unconstrained nonlinear optimization problem. Starting from the proposed cost function and making use of an approximation of the Hessian matrix, a robust modified Newton algorithm is derived. A rigorous analysis of its convergence properties is presented by using stochastic approximation theory. We also apply this theory to solve the signal reception problem of multicarrier DS-CDMA to illustrate its practical application. The simulation results show that the proposed algorithm has fast convergence and excellent tracking capability, which are important in a practical time-varying communication environment.